Lincoln Cathedral
Building continued toward the west end, unimpeded by the collapse of the tower in 1239. To ensure stability, the nave arcades were built on a continuous strip foundation which is tied transversely to the aisle walls at every pier. The piers themselves are constructed of Purbeck marble shafts around a central core, giving great strength and lightness.